The Impact of Brand Management Strategy on the Trading Companies’ Competitiveness - BIRIUKOV, Yaroslav; DUBOVYK, Tetiana; MELNYKOVYCH, Olena; NAZARYAN, Grigor; VYKHRYSTIUK, Anatolii (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).18, 2025)
The study analyses the impact of brand management strategy on the retail companies’ competitiveness in the current conditions of globalization and digital transformation. The relevance of the issue is determined by the need to create sustainable competitive advantages of companies in a highly competitive environment, where effective brand management contributes not only to enhancing consumer loyalty, but also to ensuring long-term financial stability. The aim of the study was to identify key brand management factors that affect the competitiveness of retail companies in an international context. The research used a comprehensive approach, including the methods of correlation analysis, benchmarking, and dynamic (trend) analysis. The results of the study showed that companies that invest more than 10% of total revenue in brand management demonstrate an average revenue growth of 11.4% over five years, and the customer retention rate among such companies increases by 8.2% compared to competitors. It was found that the use of digital communication platforms, social networks, and personalized marketing significantly increases the level of trust in the brand and strengthens its position in the market. The academic novelty of the study is the determined optimal combination of traditional and digital brand management tools to increase the retail companies’ competitiveness. The practical significance of the obtained results is the possibility of their application for the development of strategic marketing programmes aimed at increasing brand recognition and its adaptation to digital markets. Further research may focus on at developing methods for assessing the effectiveness of digital brand strategies in various retail segments, as well as studying the impact of new technologies, in particular artificial intelligence (AI) and blockchain.